Digestive and lung high-grade neuroendocrine neoplasms: Update and challenging issues. (June 2021) - Couvelard, Anne; Cros, Jérôme; Kasajima, Atsuko; Klöppel, Günter; Cazes, Aurélie
Abstract: High-grade neuroendocrine neoplasms (NENs) include poorly differentiated carcinomas (NECs) and well-differentiated tumors (NETs). NECs, especially LCNECs, can be difficult to distinguish from non-neuroendocrine carcinoma expressing neuroendocrine markers and from mixed NENs (called MiNENs in the digestive tract and combined carcinomas in the lung, with different criteria of definition). Recent studies on the genetic profiles of LCNECs showed that they are heterogeneous, some of them presenting the signature of site-specific adenocarcinoma. High-grade NETs, observed in digestive and thoracic organs, are only included in the digestive WHO classification, as NET G3. In the lung, they are classified among the atypical carcinoids or the LCNECs. The distinction between high-grade NET and NEC can be difficult on H&E and molecular markers may help. There is still a need for high-quality classification based on clear patho-molecular criteria, that enable the development of new therapeutic options for patients with high-grade NENs.